Propriedades estruturais e magnéticas da liga Fe50Mn25Ga25. - Andrez, Jhone Ramsay (2017)
In this work we investigated the magneto-structural properties of ????2????????, Heusler alloys. prepared by melting and then heat treated, which was subsequently subjected to cold-work processes for manufacture in the form of powder and ribbon, where changes in properties due to these cold-work were also investigated (with and without heat treatment). The analysis techniques used were X-ray diffraction, measurements of ???? magnetization as a function of applied field [??(??)] and temperature [??(??)] and also zero-field Mössbauer spectroscopy. The structural characterization indicate stabilization of a ??12 - type structure and no structural phase transformation in the studied temperature range. From the magnetic point of view, the analysis of the results suggest that while Mn atomic magnetic moments order magnetically well above 300 ??, the Fe-sublattice ordering below 300 ??, when it couples antiparallel to the Mn-sublattice, making the magnetism at lower temperatures more complex. Mechanical cold-work induces grain refinement and internal stress enhancement in the ??12 - type structure favoring antisite disorder. The present results have proof that the Fe2MnGa has its magnetic properties strongly sensitive to atomic disorder in the ??12 structure, resulting from cold-work processes. The chemical disorder favors competitions between antiferro and ferromagnetic interactions and, consequently, leading to a frustrated magnetic state when Fe and Mn subtallices ordered magnetically. Due to the chemical disorder intrinsically found in as-prepared sample or enhanced in annealed cold-work materials, we have shown (i) metamagnetic transition from antiparallel ???? and ???? coupling to a noncollinear-like magnetic state when applied field strenght is increased and (ii) a wasp-waisted magnetic loop character (measured in annealed materials) as consequence of frustration in magnetic interactions between misplaced ???? and ???? neighbors. We also demonstrated that even under similar experimental annealing conditions, the chemical disorders in as-prepared, ribbon and powder samples of the samebatch are different, producing distinct magnetic properties of the final product. Large vertical (magnetization-axis) and horizontal (field-axis) magnetization loop shifts are observed in field cooling process, and these effects may be associated with magnetic frustrated state that occurs by interaction of the two sublattices.